Opportunities and Challenges of Nanotechnology for Computer Science - Latha Mar, S.Angel; Kalaivani, E. Rama; Maheswari, K. Uma (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2015)
It was in 1959, Prof. Richard Feynman, a future Nobel prize winner delivered a visionary talk entitled, “There’s plenty of Room at the bottom”, visualizing the possibility of manipulating single atoms and molecules to produce stunning discoveries. Though at that time, Feynman’s talk looked very theoretical, now we are on the brink of actualizing that dream. This approach of atomic scale fabrication was termed by Feyman as ‘bottom up approach’, as opposed to the conventional method of ‘top down approach’ for material fabrication. According to the bottom up approach, building products with atomic precision will offer large potentials in all fields of human life. The term ‘Nanotechnology’ was introduced by Drexeler to describe Feynman’s grand vision. And it has inspired many researches to carry further the application of Nanotechnology to various scientific and application fields. Nanotechnology has been defined as the fabrication of devices with atomic or molecular scale precision. Devices with minimum features and sizes less than 100 nanometer (nm) are considered to the products of nanotechnology. As Nanotechnology enables us to organize matter at the atomic scale there are numerous fields of study that stand to gain.According to computer scientists, if the computer industry does not make radical changes to the fundamentals of computer technology, computing power will reach its physical limits. Moore’s Law states that the number of transistors that can be fitted on a chip doubles every eighteen months. However, current silicon technologies are approaching the limits imposed by quantum mechanics.